Admirable stability achieved by ns2 ions Co-doping for all-inorganic metal halides towards optical anti-counterfeiting. Issue 16 (5th April 2023) - Yang, Chuang; Guo, Fengwan; Wang, Shanping; Chen, Wenwen; Zhang, Yu; Wang, Nan; Li, Zhuozhen; Wang, Juan
Abstract : Bismuth (Bi 3+ ) and antimony (Sb 3+ ) ions codoped zero-dimensional Cs2 SnCl6 metal halide with excitation-wavelength-dependent emission is synthesized as efficient multimodal luminescence material which can be applied in anti-counterfeiting technology. Abstract : Optical materials play a momentous role in anti-counterfeiting field, such as authentication, currency and security. The development of tunable optical properties and optical responses to a range of external stimuli is quite imperative for the growing demand of optical anti-counterfeiting technology. Metal halide perovskites have attracted much attention of researchers due to their excellent optical properties. In addition, co-doping methods have been gradually applied to the research of metal halide perovskites, by which more abundant luminescence phenomena can be introduced into the host perovskite. Herein, the ns 2 ions of bismuth (Bi 3+ ) and antimony (Sb 3+ ) ions co-doped zero-dimensional Cs2 SnCl6 metal halide with an excitation-wavelength-dependent emission phenomenon is synthesized as an efficient multimodal luminescent material, the luminescence of which is tunable and covers a wide region of color. What's more, a dynamic dual-emission phenomenon is captured when the excitation wavelength changes from 320 nm to 420 nm for Cs2 SnCl6 :Bi0.08 Sb0.12 crystals. Moreover, the Bi 3+ and Sb 3+ doped metal halide material shows great enhancement in solvent resistance and thermal stability compared to the pristine Cs2 SnCl6 . The admirable stability and distinguishable photoluminescence (PL) phenomenon of this all-inorganic metal halide has great potential to be applied in optical anti-counterfeiting technology. Furthermore, the co-doping method can accelerate the discovery of new luminescence phenomena in original metal halide perovskites.